INVESTIGATION OF THERMAL EFFECTS OF RADIOFREQUENCY ABLATION MEDIATED WITH IRON OXIDE NANOPARTICLES DISPERSED IN AGAROSE AND CHITOSAN SOLVENTS - Ashikbayeva, Zhannat; Aitkulov, Arman; Wolf, Alexey; Dostovalov, Alexander; Amantayeva, Aida; Kurbanova, Aliya; Inglezakis, Vassilis J.; Tosi, Daniele (Applied Sciences., 2021)
blation (TA) is known as an alternative therapy to surgery to treat tumors. However, TA-based therapy requires advanced approaches in order to prevent causing damage to healthy tissue around the tumor and selectively target the desired area. Nanoparticles are considered as a promising tool in biomedicine to fulfill these requirements. This study was carried out in order to analyze the effect of iron oxide nanoparticles on the temperature increment during radiofrequency ablation therapy of porcine liver. In addition, this research aimed to experimentally evaluate the impact of two solvents such as agarose and chitosan on the temperature change, when magnetic nanoparticles were dispersed in them. The iron oxide nanoparticles were synthesized by the solvothermal method demonstrating the magnetic properties by acting to the external magnetic field....
Keywords: radiofrequency ablation; iron oxide magnetic nanoparticles